Microstructure and texture development in (FeCoCrNi)94Al2Ti4 alloy processed by asymmetric hot-rolling - Guojun Cai; Yanru Huang; Yongquan Qing; R.D.K. Misra (Journal of Materials Research and Technology)
Microstructure and texture development in (FeCoCrNi)94Al2Ti4 high-entropy alloy were investigated by adopting asymmetrical hot rolling (ASHR) technology proceeded different velocity ratio. It was found that the grain refinement and recrystallization behavior were particularly obvious with increasing velocity ratio and reduction due to improved shear deformation. The high cross-shear under ASHR condition produced a positive shear strain throughout the entire thickness, and the increase in velocity ratio of working rolls led to intense Brass {011}<211> component which was retained after annealing. Meanwhile R-Copper {112}<110> and R-Cube {001}<110> orientations were changed into Brass {011}<211> orientation and γ-fiber textures such as {111}<110> and {111}<112> components. The excellent mechanical properties of (FeCoCrNi)94Al2Ti4 alloy with a yield strength of 1191 MPa, ultimate tensile strength of 1394 MPa and total elongation of 27.1% were attributable to effective grain refinement at high velocity ratio, while the significant improvement of formability was governed by increased intensities of Brass {011}<211> and γ-fiber textures.